Risk and Resilience in the Halal Supply Chain: A Bibliometric Review of Themes, Technologies, and Governance - Farras, Joval Ifghaniyafi; Kaltum, Umi (Fakultas Tarbiyah dan Ilmu Keguruan, IAI Sultan Muhammad Syafiuddin, 2025)
Ensuring halal integrity from source to shelf introduces distinctive risk exposures, including contamination, fraud, and certification gaps, and requires resilience capabilities that safeguard both religious compliance and operational continuity. This bibliometric review maps the intellectual structure of halal supply chain research on risk and resilience using science mapping outputs, including keyword co occurrence network, overlay, and density visualizations.Three major knowledge domains emerge. The first centers on technology enabled integrity, including blockchain, traceability systems, RFID, and smart contracts. The second focuses on assurance and governance, encompassing halal certification, Shariah compliance, institutional mechanisms, and trust formation. The third domain addresses logistics and operations, particularly halal logistics and food safety management. Overlay visualization reveals a temporal shift toward digitally mediated transparency, especially blockchain and artificial intelligence applications, alongside sustainability as more recent research priorities. Density mapping identifies “halal,” “blockchain,” “traceability,” “halal supply chain,” and “food safety” as enduring conceptual anchors within the field.